3(3x-2)=2(2x+1)

Simple and best practice solution for 3(3x-2)=2(2x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3x-2)=2(2x+1) equation:


Simplifying
3(3x + -2) = 2(2x + 1)

Reorder the terms:
3(-2 + 3x) = 2(2x + 1)
(-2 * 3 + 3x * 3) = 2(2x + 1)
(-6 + 9x) = 2(2x + 1)

Reorder the terms:
-6 + 9x = 2(1 + 2x)
-6 + 9x = (1 * 2 + 2x * 2)
-6 + 9x = (2 + 4x)

Solving
-6 + 9x = 2 + 4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-4x' to each side of the equation.
-6 + 9x + -4x = 2 + 4x + -4x

Combine like terms: 9x + -4x = 5x
-6 + 5x = 2 + 4x + -4x

Combine like terms: 4x + -4x = 0
-6 + 5x = 2 + 0
-6 + 5x = 2

Add '6' to each side of the equation.
-6 + 6 + 5x = 2 + 6

Combine like terms: -6 + 6 = 0
0 + 5x = 2 + 6
5x = 2 + 6

Combine like terms: 2 + 6 = 8
5x = 8

Divide each side by '5'.
x = 1.6

Simplifying
x = 1.6

See similar equations:

| -7(1-2x)+6(x-2)= | | 2r+5r+13= | | T=18x+6 | | -2/3(6/5x7/10)=17/20 | | -36=-9v | | 4-5(5-4x)= | | 4g+2(-3+4g)=1-g | | 35313=x(x*0.16) | | 8(6+x)-10(5-4x)=-98 | | -8(-3m-3)-7m= | | m/n=7.3 | | 30=7(y-5)+6 | | 2(3x+5)=76 | | 12(5+2y)=4y-(6-8y) | | -18=c-5 | | -2(7x+1)=14-6x | | 200=xl | | x=35313(35313*0.16) | | 6z+7=5z+6 | | 400/460 | | m-(-18)=7 | | -5x-4-5x=-24 | | 7-3y+6=-7 | | 9=5+2g | | -4(6n-4)-7= | | ax^2-bx^2=0 | | 16+c=-5 | | 1+4a-a= | | 15y+3x=61 | | 0=-16t^2+24t+40 | | 4+2q=8 | | 5n+3=4-6(6-5n) |

Equations solver categories